Meningkatkan Kesehatan Mental Generasi Alpha Melalui Permainan Engklek - Febe Andiyani Putri; Refni Fajar Wati Zega (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The alpha generation already exists in the scope of life now and can be found throughout the world, the focus of discussion now is the concern for the mental well-being of the alpha generation who have been born and grown in the world of technological advances. This research was conducted to find solutions in improving the mental health of alpha generation children, namely the main focus on early childhood with the method of the traditional game engklek. Researchers used a descriptive qualitative method with a literature study approach, namely collecting data and information through books, the internet, and science journals. By playing traditional games, alpha generation early childhood children have other activities or activities that can be done besides playing gadgets, so that cricket games have a role in improving children's mental health and physical health. With the results of this study, it is hoped that schools and parents will pay more attention to children's mental health and provide other solutions to overcome alpha generation children who play gadgets more often, namely by reviving traditional games.